Election fraud and privacy related issues: addressing electoral integrity - Lubis, Muharman; Kartiwi, Mira; Zulhuda, Sonny (Institute of Electrical and Electronics Engineers Inc., 2017)
Nowadays, in a highly computerized system, people have tendency to have not expect privacy to be maintained and continue in its current form if individual control is required and monitored. Especially, in contemporary campaigns for higher office, the candidates often use mass media to deliver political message or having certain campaign developed by expert in the efficient use of providing personal information for the purpose of influencing the voters while some of them may be hidden or exploited by certain parties. Practically, it is impossible to have total control over personal information, once it has been collected and dispersed but it is possible to have privacy without control and vice versa. In election, huge amount of data is stored and transfer from multiple location to other numerous or single location to facilitate tabulation and calculation analysis. Thus, it is critical to conduct monitoring process to prevent crime such as theft, fraud and illegal use, to prevent unauthorized disclosure of confidential information, to comply with the obligation, law and regulation in avoiding discrimination, to maintain productivity and quality of service and to ensure integrity of the systems. This paper explores the election fraud and privacy related issues occurred during the election period in various countries to address the electoral integrity in Indonesia.